Utilization of Fathers’ Fortes when Parenting: Analyzing their Perspectives and Experiences in a Focus-Group Interview Format - et. al., Sung Hee Hong , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study attempted to explore the methods that fathers tend to apply when parenting their children, particularly from their own perceptions and experiences of applying their fortes or strengths. In the study, six fathers residing in Busan and Southern Gyeongsang Province located in South Korea. As a studying method, the researchers implemented a ‘focus group interview’ with the six participants in which a series of in-depths discussions occurred to draw their opinions and ideas as they made interactions. The researchers placed three participants in each of two groups, and each group had two 2-hours-long sessions. The results reflected how the participants perceive their fortes, which then had been categorized into four aspects: namely, i) full usage of fortes when parenting, ii) discovering their fortes and successfully playing their roles, iii) reinforcing their fortes and supplementing weaknesses, and iv) adapting to the fast-changing social requirements for fathers. The findings implied that rather than performing a problem-solving approach, the supports for fathers need to be based on their fortes.